The bitter end - Donne, Alexa (New York : Random House, 2024)
Students from an elite prep school travel to a remote ski cabin for their senior excursion, but as the temperature drops and a blizzard traps them inside, tensions rise, secrets and betrayals are revealed, and when classmates begin to die, the group must uncover the killer among them to survive.
Ages 14 and up.
Grades 10-12.
Keywords: Preparatory school students -- Juvenile fiction; Murder -- Juvenile fiction; Vacations -- Juvenile fiction; Survival -- Juvenile fiction; Young adult fiction; Detective and mystery fiction; Thrillers (Fiction)